2017
DOI: 10.2903/j.efsa.2017.5113
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of some aspects related to genotoxicity assessment

Abstract: The European Commission requested EFSA to provide advice on the following: (1) the suitability of the unscheduled DNA synthesis (UDS) in vivo assay to follow-up positive results in in vitro gene mutation tests; (2) the adequacy to demonstrate target tissue exposure in in vivo studies, particularly in the mammalian erythrocyte micronucleus test; (3) the use of data in a weight-of-evidence approach to conclude on the genotoxic potential of substances and the consequent setting of health-based guidance values. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 12 publications
0
86
0
1
Order By: Relevance
“…Accordingly, the UDS test may be an appropriate test to detect DNA damage after exposure to chemicals that specifically target the liver (as both target organ of toxicity and main metabolic site; Corvaro and Bartels ) and that were positive in the Ames test. This responds also to the most restrictive interpretation criteria for this test (e.g., Hardy et al ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Accordingly, the UDS test may be an appropriate test to detect DNA damage after exposure to chemicals that specifically target the liver (as both target organ of toxicity and main metabolic site; Corvaro and Bartels ) and that were positive in the Ames test. This responds also to the most restrictive interpretation criteria for this test (e.g., Hardy et al ).…”
Section: Discussionmentioning
confidence: 91%
“…This study is accepted as higher tier follow‐up for mutagenicity in most geographies. However, recently in various pieces of the literature, the value of this test as a follow‐up for mutagenicity has been criticized (Kirkland and Speit ; OECD ; Hardy et al ). According to these documents, the test, in fact, responds positively only to chemicals that induce the type of DNA damage that is repaired by nucleotide excision (mainly bulky adducts) and does not detect mutagenic consequences of the unrepaired genetic damage.…”
Section: Discussionmentioning
confidence: 99%
“…If at least one of the in vitro tests indicates genotoxic activity, or if it is not appropriate to test the nanomaterial in vitro (e.g. if the dispersion medium is not compatible with the in vitro system), this normally requires follow-up by in vivo testing (Eastmond et al, 2009;EFSA Scientific Committee, 2011b, 2017d, unless it can be adequately demonstrated by other means that the positive in vitro findings are not relevant for the in vivo situation. It has to be noticed that inflammatory effects induced by nanomaterials can generate reactive radical species, potentially triggering secondary genotoxicity that cannot be detected by in vitro systems.…”
Section: 4mentioning
confidence: 99%
“…It should be related to the genotoxic endpoint(s) identified as positive in vitro and performed on appropriate target organ(s) or tissue(s). As outlined in the EFSA Genotoxicity testing strategies (EFSA Scientific Committee, 2011a, 2017d, in vivo genotoxicity testing should be performed in a step wise approach depending on the outcome of the in vitro tests. Accordingly, the following in vivo tests testing may be suitable:…”
Section: 4mentioning
confidence: 99%
“…A complete package of genotoxicity studies for ( EZ )‐1,3‐dichloropropene. These studies should be performed with the new technical specification, and in accordance with EFSA Scientific Committee (, ) (relevant for all representative uses evaluated; submission date proposed by the applicant: unknown, see Section 2). The potential for endocrine‐disrupting properties of ( EZ )‐1,3‐dichloropropene investigated on the basis of the available data and current knowledge, i.e.…”
Section: Data Gapsmentioning
confidence: 99%